Pain And Anxiety During AV Fistula Cannulation Among Hemodialysis Patients - Fareed, Laila; Saeed, Arslan Akbar; Ahmed, Yahya Azeem (Biological and Clinical Sciences Research Journal, 2025)
AV fistula cannulation is a routine yet often painful and anxiety-inducing procedure for patients undergoing maintenance hemodialysis. Despite its frequency, procedural pain and psychological distress remain under-addressed, especially in low-resource settings like Pakistan. Objective: To assess the severity and prevalence of pain and anxiety during AV fistula cannulation among hemodialysis patients in a tertiary care hospital in Pakistan. Methods: This cross-sectional descriptive study was conducted at the Dialysis Unit, Department of Nephrology, Nishtar Hospital Multan, from 15 December to 15 March. A total of 135 patients undergoing maintenance hemodialysis through AV fistula were included. Pain was evaluated using the Visual Analog Scale (VAS), and anxiety was measured using the Hospital Anxiety and Depression Scale – Anxiety subscale (HADS-A). Data were analyzed using SPSS v25, with chi-square tests for statistical significance (p<0.05). Results: Pain during cannulation was reported by 92.6% of patients, with 28.1% experiencing mild, 38.5% moderate, and 25.9% severe pain. Anxiety was present in 62.9% of patients (31.1% mild, 20.7% moderate, 11.1% severe). Significant associations were found between anxiety and female gender (p<0.05), as well as between severe pain and longer dialysis duration (p=0.032). Conclusion: Pain and anxiety are highly prevalent during AV fistula cannulation among Pakistani hemodialysis patients. Integrating pain management and psychological screening into routine dialysis care may significantly improve the well-being of this vulnerable population.